2009
DOI: 10.1111/j.1751-9004.2009.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Body in Mind: The Role of Embodied Cognition in Self‐Regulation

Abstract: We review a growing body of literature that evidences the reciprocal relationship between body and mind, known as embodied cognition. We argue that an embodied mind may serve a functional purpose, aiding in self-regulatory processes. Specifically, we suggest that embodied cognition assists in self-regulation by increasing signal strength, encouraging appropriate goal-relevant action, and incorporating situational constraints to cue appropriate information processing styles. Furthermore, we propose that affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 78 publications
(77 reference statements)
1
24
0
Order By: Relevance
“…Recent research shows that goals need not be specific, as long as plans are, and that writing about life goals and plans in a structured way is especially effective (Locke and Schippers, 2018; for a review see Morisano et al, 2010;Morisano, 2013;Schippers et al, 2015;Travers et al, 2015). As goal-relevant actions may be encouraged by embodied cognition, and embodied cognition has been related to (dynamic) self-regulation, this may be the process through which written goals lead to action (see Balcetis and Cole, 2009). Specifically, through the link between cognition and behavior, it can be seen as beneficial to write down intended actions as this will lay the path to act out the intended actions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research shows that goals need not be specific, as long as plans are, and that writing about life goals and plans in a structured way is especially effective (Locke and Schippers, 2018; for a review see Morisano et al, 2010;Morisano, 2013;Schippers et al, 2015;Travers et al, 2015). As goal-relevant actions may be encouraged by embodied cognition, and embodied cognition has been related to (dynamic) self-regulation, this may be the process through which written goals lead to action (see Balcetis and Cole, 2009). Specifically, through the link between cognition and behavior, it can be seen as beneficial to write down intended actions as this will lay the path to act out the intended actions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, through the link between cognition and behavior, it can be seen as beneficial to write down intended actions as this will lay the path to act out the intended actions. The processing of the language facilitates the actions, as it consolidates the imagined actions (Addis et al, 2007;Balcetis and Cole, 2009;Peters et al, 2010;Meevissen et al, 2011). It has been suggested that goal-relevant actions may be encouraged by embodied cognition, through the process of self-regulation (Balcetis and Cole, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals frequently use embodied cues for functional self-regulatory purposes (Balcetis and Cole, 2009 ; Schnall et al, 2010 ; Bargh and Shalev, 2012 ; Shalev, 2014 ). However, using embodied cues as diagnostic inputs (Williams et al, 2009 ; Ackerman et al, 2010 ; Meier et al, 2012 ; Robinson and Fetterman, 2015 ; Winkielman et al, 2015 ) may lead to human-robot miscommunications.…”
Section: Addressing the Human-robot Communication Gap Over Goal Pursumentioning
confidence: 99%
“…E Balcetis & S. Cole (2009). 'Body in Mind: The Role of Embodied Cognition in Self-Regulation' Social and Personality Psychology Compass 3:5. pp.…”
mentioning
confidence: 99%